Evolving Toward Subject-Specific Gait Rehabilitation Through Single-Joint Resistive Force Interventions - Iyer, S. Srikesh; Joseph, Joel V.; Vashista, Vineet (Frontiers in Neurorobotics, 2020)
Walking is one of the most relevant tasks that a person performs in his daily routine. Despite its mechanical complexities, any change in the external conditions that applies some external perturbation or in the human musculoskeletal system that limits an individual's movement entails a motor response, which can either be compensatory or adaptive in nature. Incidentally, with aging or due to the occurrence of a neuro-musculoskeletal disorder, a combination of such changes are reported including reduced sensory perception, muscle weakness, spasticity, etc. that significantly degrade the human walking performance. Various studies in the gait rehabilitation literature have identified a need to develop better rehabilitation paradigms and have implied on the critical role of an efficient human robot interaction. Understanding how humans respond to a particular gait alteration can be beneficial in designing an effective rehabilitation paradigm. In this context, the current work investigates human locomotor adaptation to resistive alteration to the hip and ankle strategies of walking. A cable-driven robotic system, which does not add mobility constraints, is used to implement resistive force interventions about the hip and ankle joints separately through two experiments with eight healthy adult participants in each. In both cases, the intervention was applied during the push-off phase of walking, i.e., from pre-swing to terminal swing. The results showed that subjects in both groups adopted a compensatory response to the applied intervention and demonstrated intralimb and interlimb adaptation. Overall, the participants demonstrated a deviant gait implying lower limb musculoskeltal adjustments as if to compensate for a hip or ankle abnormality.